Analysis of Collaborative Governance in Managing Ketapang Urban Aquaculture (KUA) Tourism Village in Tangerang Regency: Analisis Collaborative Governance dalam Pengelolaan Desa Wisata Ketapang Urban Aquaculture (KUA) di Kabupaten Tangerang - Laeli Nur Khanifah; Bintang Kamila Maharani (Jurnal Pemerintahan dan Politik, 2026)
Objective This study aims to analyze the implementation of collaborative governance in the management of Ketapang Urban Aquaculture following the transfer of management from the village government and local community to a Regional-Owned Enterprise (BUMD), as well as to examine its impact on inter-actor relations, community participation, and the socio-economic conditions of the local community. Methods a qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and document analysis. Methodological triangulation was applied to ensure data validity. Findings The findings indicate that the transfer of management has led to a more centralized and corporatized governance structure, which has resulted in decreased community participation, weakened social integration, and a decline in local economic activities, particularly among MSMEs. Furthermore, the implementation of collaborative governance remains suboptimal, as reflected in limited inter-actor communication, imbalanced roles, low levels of trust, and the absence of shared understanding in tourism management. Implications This study highlights the importance of improving governance through strengthening inclusive community participation, enhancing transparency and accountability, and optimizing the role of government as a facilitator in bridging the interests of various stakeholders. Originality This study provides an empirical contribution to the collaborative governance literature by demonstrating that the involvement of semi-government actors such as BUMD does not necessarily strengthen collaboration, but may instead create power imbalances if not supported by participatory and transparent mechanisms. It also emphasizes that weaknesses in one dimension of collaboration can have systemic effects on the overall governance process and its outcomes.